IMPLEMENTASI METODE FUZZY TIME SERIES CHEN UNTUK PERAMALAN JUMLAH PENGUNJUNG MUSEUM - Ni’matul Azizah, Alfin; Sucipto , Hadi; Ali , Mahrus (Inovate, 2025)
Forecasting or prediction is a technique utilize to anticipate future indefiniteness in an attempt to make more effective judgement. Fuzzy Time Series is the latest approach in preparation brilliance that is utilize to predict propositions by translating annals data into linguistic values ​​and producing more precise predictions. This research discusses the fuzzy time series system developed by Chen (1996) to predict the number of visitors to the Indonesian Islamic Museum Hasyim Asy'ari Tebuireng Jombang (MINHA) in July 2024. In fuzzy time series, the extensive of the interval greatly influences the predictions results. The system for quotation the extensive of the interval used in this study uses Sturges' rule, predicting the number of visitors to the MINHA museum based on data for June 2022 - April 2024, the forecast results for May were 1390,583 with a MAPE value of 21.27, while the forecast for June produced a forecast of 17,204,417 months. July produced forecasts of 14566.15 with a MAPE value of 24.77 which was included in the feasible forecasting category. Keywords: Forecasting, Fuzzy Time Series, Chen , Number of visitor